Inducible clindamycin resistance among clinical isolates of staphylococci - Ciraj A; Vinod P; Sreejith G; Rajani K (Wolters Kluwer Medknow Publications, 2009)
Introduction: Clinical failure of clindamycin therapy has been reported due to multiple mechanisms that confer resistance to macrolide, lincosamide and streptogramin antibiotics. This study was undertaken to detect the presence of inducible clindamycin resistance among clinical isolates of staphylococci. Materials and Methods: The detection of inducible clindamycin resistance was performed by D-test using erythromycin and clindamycin discs as per CDC guidelines. Results: Among the 244 clinical isolates of staphylococci studied, 32 (13.1%) showed inducible clindamycin resistance and belonged to the MLSBi phenotype. Among the MLS B i phenotypes, 10 isolates were methicillin-resistant Staphylococcus aureus (38.4% of the total MRSA), 16 were methicillin-sensitive Staphylococcus aureus (12.9% of the total MSSA) and 6 were coagulase-negative staphylococci (6.3% of the total CONS). Conclusion: The test for inducible resistance to clindamycin should be included in the routine antibiotic susceptibility testing, as it will help in guiding therapy.